Evaluation the Effect of Disclusion time Reduction (DTR) in Management Myofacial Pain Syndrome in Iraqi Patients Using the Digital Occlusal Analysis (T-scan) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The aim of the study is to evaluate the effectiveness of disclusion time reduction in treatment of myofacialpain syndrome using immediate complete anterior guidance development (ICAGD) protocol monitoredby digital occlusal analysis (T-scan). Methods and materials: Subjects with full dentition and angle classI relation. DC/TMD criteria were used to diagnose the patients with various MFDS symptoms includingmouth opening (assisted and unassisted), excursion movements (mediotrusion and protrusion) and painfulmasticatory muscles involvement. A visual analog scale was used to assess the pain intensity. DisclusionTime Reduction (DTR) of all molars and premolars to < 0.5 second on all studied locations include: (Centricrelation, Maximum intercaspation, Right lateral, left lateral and protrusion) have been made, the patientswere recalled tow times at the 7th day and 14th day for the follow up and the subjects were assessed for thesymptoms relief. Results: Highly significant difference P? 0.001 in period (1st day pretreatment -7th daypost treatment) and(1st day pretreatment- 14th day post treatment) related to changes in disclusion timeand all symptoms of MFDS but in period (7th day post treatment -14th day post treatment) ,the data outsidethe comparison limited (OCL) was stated according to the pain intensity, mouth opening (assisted andunassisted)and excursion movements while a non- significant difference P>0.05 were documented relatedto changes in disclusion time and painful masticatory muscle involvement . Conclusion: The results showedthe DTR less than 0.5 seconds reduces musculoskeletal-based symptoms of MFDS patients, and this methodcan be used clinically with highly success in treatment MPDS.